SPE Improved Oil Recovery Symposium 2014
DOI: 10.2118/169136-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Alternative to Core Plug Tests for Optimising Injection Water Salinity for EOR

Abstract: Core tests have demonstrated that decreasing the salinity of injection water can increase oil recovery. Although recovery is enhanced by simply decreasing salt content, optimising injection water salinty would offer a clear economic advantage for several reasons. Too low salinity risks swelling of the clays which would lead to permanent reservoir damage but evidence of effectiveness at moderate salinity would offer the opportunity to dispose of produced water. The goal is to define boundary conditions so injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Our AFM results show that increasing pH from 7 to 11 indeed decreased 80% of the adhesion force for both functional groups, confirming that low salinity water likely lifts off oil films from pore surfaces thus increasing water-wetting. Similar results were also observed by Hassenkam et al, ,, who measured adhesion force of a model oil on sandstone grains and model rocks using AFM. Their results show that low salinity water decreases the adhesion force between the model oil and both types of rock, implying that adhesion force reduction of oil and rock surface in the presence of low salinity water can be achieved at pore surfaces in reservoirs.…”
Section: Resultssupporting
confidence: 88%
“…Our AFM results show that increasing pH from 7 to 11 indeed decreased 80% of the adhesion force for both functional groups, confirming that low salinity water likely lifts off oil films from pore surfaces thus increasing water-wetting. Similar results were also observed by Hassenkam et al, ,, who measured adhesion force of a model oil on sandstone grains and model rocks using AFM. Their results show that low salinity water decreases the adhesion force between the model oil and both types of rock, implying that adhesion force reduction of oil and rock surface in the presence of low salinity water can be achieved at pore surfaces in reservoirs.…”
Section: Resultssupporting
confidence: 88%
“…On experiments in sandstone, the low salinity response can clearly be observed using CFM on treated and fresh samples. Hassenkam and colleagues and Matthiesen and colleagues demonstrated that overall adhesion and the low salinity response are strongly influenced by the organic materials that are naturally present on all mineral surfaces, even when they have never been in contact with oil or gas. In several experiments with the same conditions as presented in this study, the average adhesion on grains from sandstone that had been solvent treated was ∼110 pN, which is comparable to the average adhesion obtained in our study on the treated sample, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…There is general agreement that divalent ions must be present in the formation water, polar components are required in the crude oil, and the presence of clay in the reservoir is essential. ,, It has not yet been established if these requirements also hold for carbonate rocks. Previous work has demonstrated the effectiveness of atomic force microscopy (AFM), in chemical force mapping (CFM) mode, for observing changes in surface wettability that result from changing the salinity of the solution in contact with mineral grains from sandstones. ,,, The experiments used AFM tips functionalized with molecules ending in methyl (−CH 3 ) to make them hydrophobic or carboxyl (−COO­(H)) to make them polar, either neutral or acidic, depending on the pH of the solution. A change toward slightly more water wet pore surfaces has been suggested as one of the main causes for the low salinity response .…”
Section: Introductionmentioning
confidence: 99%